PENGUJIAN KINERJA JARINGAN SISTEM AKSES FILE BERBASIS CLIENT SERVER MENGGUNAKAN SAMBA SERVER - Kusumaningrum, Anggraini (Sekolah Tinggi Teknologi Adisutjipto, 2016)
Data communication is the process of exchanging data between two or more devices through a transmission medium such as a cable. In order for the data communication can occur, the device must be connected to communicate with each other or be a part of a communication system consisting of hardware (hardware) and software (software). Samba server is a software bridge between the two operating systems that run within a computer network. Samba is able to share files with computers that use operating system linux, unix and windows with a peer to peer system. The time needed on the LAN network access system based on client file servers using Samba server with a minimum file size of 3MB and a maximum of 1GB for the download process is 04 minutes 54 seconds while the upload is 09 minutes 24 seconds. Speed transfer rate that is produced with a minimum file size of 3MB and a maximum of 1GB for the download process is 4.762Kbps and to upload is 1.896Kbps. On QoS testing conducted on 5 PCs, 10PC, 15pc and client 20PC result more and more PC client that accesses 1 file the success rate will be getting worse, it is because the bottleneck on the network.Kata Kunci : Network, client server, Samba Server